PERLINDUNGAN HUKUM TERHADAP ISTRI SEBAGAI KORBAN KEKERASAN DALAM RUMAH TANGGA SECARA FISIK YANG DILAKUKAN OLEH SUAMI - Titik Sugianti (Constitutum: Jurnal Ilmiah Hukum, 2024)
Domestic violence is a crime against human dignity and is a form of discrimination that must be eliminated. Domestic violence is not a domestic (private) problem that should not be known by anyone because women have the same rights to be free and determine their desires in life according to norms. One of the causes of domestic violence is economic problems. This study aims to determine the implementation of protection for wives as victims of domestic violence. This study is a normative legal study that uses secondary data. The results of this study indicate that protection for wives as victims of domestic violence refers to Law Number 23 of 2004 concerning the Elimination of Domestic Violence, namely through temporary security from the police and/or personal protection, placement of victims in "safe houses" and recovery periods, physical and mental care, and efforts to suppress perpetrators of domestic violence. However, regulations aimed at protecting victims of domestic violence have not been fully implemented by law enforcement officers.